Thermal expansion of MWCNT-reinforced copper composite - 许龙山 陈小华 潘伟英 李文华 杨植 蒲玉兴 易国军 易斌 张科 (Transactions of Nonferrous Metals Society of China, 2007)
Multi-walled carbon nanotube （MWCNT）-reinforced copper composite was fabricated by a novel method, which involves solution phase synthesis of MWCNT-implanted cuprous oxide composite spheres, formation of MWCNT/copper composite spheres after reduction in H2 atmosphere and preparation of the MWCNT/copper bulk with vacuum hot pressing. The SEM images of the fracture surfaces indicate that MWCNTs are homogeneously dispersed in the composite and bonded to the matrix. In addition, the thermal expansion of the composites with various MWCNT contents （0%, 1% and 5%, mass fraction） were investigated. The coefficient of thermal expansion （CTE） decreases with increasing MWCNT content, which are all much lower than that of pure copper.